Music syllabus for use in secondary schools based on materials drawn from Philippine music - Aurelio, Mary Lou Fermin (1991)
This study was concentrated on the development and evaluation of a music syllabus for use in secondary schools based on materials drawn from Philippine music. It includes Philippine music which can be used effectively to achieve musical skills and knowledge and at the same time instilling a love for one's own culture. It constitutes the corresponding formative and summative test materials drawn through the "R and D cycle".
Thesis (Ed.D.)--Mariano Marcos State University.
Keywords: Music -- History and criticism -- Philippines -- Outlines, syllabi, etc; Education, Secondary -- Activity programs -- Philippines